Pathways to Recovery: development and evaluation of a cognitive–behavioural therapy in-patient treatment programme for adults with anorexia nervosa. (23rd April 2018) - Brown, Andrea; Jenkinson, Richard; Coakes, Julia; Cockfield, Annette; O'Brien, Tish; Hall, Louise
Abstract : Aims and method: A cognitive–behavioural therapy in-patient treatment model for adults with severe anorexia nervosa was developed and evaluated, and outcomes were compared with the previous treatment model and other published outcomes from similar settings. Results: This study showed the Pathways to Recovery outcomes were positive in terms of improvements in body mass index and psychopathology. Clinical implications: Adults with anorexia nervosa can achieve good outcomes despite longer illness duration and comorbidities. Declaration of interest: A.B., A.C. and L.H. work at The Retreat where the Pathways to Recovery were developed.